2023
DOI: 10.1021/acscatal.3c00337
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Oxygen Evolution Reaction on Fe3O4(001) with Single-Atom Catalysts

Abstract: Doping magnetite surfaces with transition-metal atoms is a promising strategy to improve the catalytic performance toward the oxygen evolution reaction (OER), which governs the overall efficiency of water electrolysis and hydrogen production. In this work, we investigated the Fe 3 O 4 (001) surface as a support material for single-atom catalysts of the OER. First, we prepared and optimized models of inexpensive and abundant transitionmetal atoms, such as Ti, Co, Ni, and Cu, trapped in various configurations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
(191 reference statements)
0
9
0
Order By: Relevance
“…The OER is an unwanted side reaction in NiO x alkaline batteries, and it has long been found that Fe impurities enhance such a process, [66][67][68][69] with this attracting significant attention to the effects of Fe-doping in NiO x electrodes for OER electrocatalysis in alkaline media. Many studies have indeed shown that Fedoped nickel oxides are promising electrocatalysts for the OER.…”
Section: Li-layered Co-based Alloy Oxidesmentioning
confidence: 99%
“…The OER is an unwanted side reaction in NiO x alkaline batteries, and it has long been found that Fe impurities enhance such a process, [66][67][68][69] with this attracting significant attention to the effects of Fe-doping in NiO x electrodes for OER electrocatalysis in alkaline media. Many studies have indeed shown that Fedoped nickel oxides are promising electrocatalysts for the OER.…”
Section: Li-layered Co-based Alloy Oxidesmentioning
confidence: 99%
“…6 Transition metals (TMs), especially 3d metals, are the best option as OER catalysts due to their high abundance, affordable price, and high catalytic activity. 7 Among them, nickel is predicted to be the most efficient one. [8][9][10] From the materials science point of view, many efforts have been made in order to improve the performance of TM-based catalysts by modifying their morphology, structure and size, since a strong dependence on their physical form has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…6 Transition metals (TMs), especially 3d metals, are the best option as OER catalysts due to their high abundance, affordable price, and high catalytic activity. 7 Among them, nickel is predicted to be the most efficient one. 8–10…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, magnetic coral-like Fe 3 O 4 nanoparticles were investigated at different calcining temperatures, displaying the best performance with an overpotential of 234 mV and Tafel slope of 100 mV dec –1 at 450 °C . In a recent theoretical study carried out on the Fe 3 O 4 (001) surface for OER, transition-metal atoms including Co, Cu, Ni, and Ti have been doped on the magnetic surface, and results have predicted an overpotential of about 350 mV for Co-doped Fe 3 O 4 surface in alkaline solution . Immobilized Fe 3 O 4 nanoparticles on Ni-based MOFs (metal–organic frameworks) displayed an overpotential of 295 mV at 10 mA/cm 2 and a Tafel slope of 47.8 mV dec –1 .…”
Section: Introductionmentioning
confidence: 99%